Study Preparation of Refugees in Germany: How Teachers’ Evaluative Practices Shape Educational Trajectories - Schröder, Stefanie (Social Inclusion, 2021)
Recent research shows that a remarkable share of refugees who have arrived in Germany over the past few years is highly qualified and has strong educational and academic aspirations. Preparatory colleges (Studienkollegs) and language courses of higher education institutions are the two main organisations providing obligatory study preparation for non‐EU international study applicants in Germany, including an increasing number of refugees. So far, research on conditions for refugees’ successful transitions into and through study preparation, and eventually into higher education, is scarce. The article fills a research gap on the organisational level by considering the established norms and rules of study preparation organisations and the key role of teachers in shaping successful pathways into higher education. Based on central concepts deriving from the sociology of valuation and evaluation, categorisation, and evaluative repertoires, the article aims to illustrate the organisational norms and rules in play shaping teachers’ experiences and perceptions of their students’ ability to study. The qualitative analysis of seven expert interviews shows how teachers differentiate between students with and without a refugee background in terms of performance and reveals opportunities and constraints to take refugees’ resources and needs in study preparation programmes into account.